PROTOTIPE MONITORING KETINGGIAN AIR BENDUNGAN MELALUI MEDIA SOSIAL TWITTER BERBASIS MIKROKONTROLER ATMEGA-328PU - Arnawa, I G.M Sugiri; Raka AGung, I . G. A. (Jurnal Teknologi Elektro, 2015)
The prototype of this dam water level monitoring function to provide information about the dam water level through social media twitter and speakers. Information on twitter social media can be found by following the twitter account of this tool . The prototype consists of a microcontroller Arduino Uno , HC - SR04 sensor , LCD , WTV020SD and the Ethernet Shield . Sensor HC - SR04 , read the value of the dam water level based on emission and reflection of ultrasonic waves . Arduino Uno microcontroller will process and display the sensor input from HC - SR04 form of dam water level on the LCD and sent via ethernet shield to social media twitter . WTV020SD serves to ring the speaker on the water level 10 cm , 20 cm , 30 cm and 40 cm . The sound emitted is the normal condition of the dam , flood alert , flood alert and flood . Water level measurement results on LCD , manual measurement and display on twitter social media have gotten the same results .
Keywords: rduino; Ethernet; HC-SR04; WTV020SD.